Bad Mexican : portrayal of corruption and the drug trade in Man on Fire, Traffic, and La Ley de Herodes. - Goh, Dianne. (2011)
By victimizing the United States and demonizing Mexico, Hollywood films such as Traffic and Man on Fire create stereotypes of Mexicans based on the drug trade and corruption in Mexico so the United States can define its identity and become Mexico’s saviour. This essay will point out how Hollywood is limited in its perspective of the drug trade and corruption in Mexico, and how Mexico is facing a real problem that is more than just a Hollywood stereotype. It is my hope that audiences will realize this and not depend totally on Hollywood films to gain knowledge about Mexico. To examine how the drug trade and corruption are portrayed in Hollywood films, Traffic and Man on Fire are typical examples of how Hollywood creates stereotypes of Mexicans as corrupt drug dealers to affirm the United States’ identity as a superior society and as saviours of Mexico. But according to La Ley de Herodes, Mexico is not interested in being saved, and it does not portray corruption in terms of Hollywood’s definitions of them. Therefore, this essay will critically analyze and compare how Mexican and Hollywood films portray the drug trade and corruption in Mexico, and what the implications are.